Contrasting the Usage of Punctuations in Chinese and Indonesian Language - Asmuliyati Nahnu; Ria Riski Marsuki (Universitas Negeri Semarang, 2023)
Knowing the punctuation marks in Chinese and Indonesian is very important. Therefore, in order to avoid mistakes or inaccuracies in the use of punctuation marks, this research was conducted to clearly describe the similarities and differences in the use of punctuation marks in Mandarin and Indonesian.This study is a descriptive qualitative research using the literature method and the contrastive analysis method. The results show that of the 12 punctuation marks in this study, there are 7 punctuation marks that have the same form and use, 3 punctuation marks that have different forms with the same use, and there are 2 punctuation marks in Mandarin that are not found in Indonesian.